The state of the atmosphere in the city of Krasnoyarsk (Russia) in indicators of sustainable development. Issue 4 (18th May 2020) - Shaparev, N.; Tokarev, A.; Yakubailik, O.
ABSTRACT: The article deals with the state of the atmosphere of Krasnoyarsk (Russia) over the period 2007–2017 in the indicators of sustainable development adopted by the UN, developed in the USA and Russia. For this purpose, data from annual State reports on the state of the environment and recordings from automated city monitoring stations are used. The dynamics of gross emissions of pollutants into the city atmosphere, the annual state of air quality and air quality in real time in 2018 are analyzed. The dependence of the Air Quality Index on weather conditions is investigated.